EVALUASI PENGGUNAAN LISTRIK PADA BANGUNAN GEDUNG DI LINGKUNGAN UNIVERSITAS TADULAKO - Baso Mukhlis (Foristek, 2011)
This study aims to determine the level of energy use and savings opportunities that can be obtained from a room based on IKE value. The intensity of energy consumption (IKE) is a term that used to determine levels of energy consumption in a building. IKE value is calculated based on the number of electric power used by all existing electrical equipment in a room and then divided by the area of the room. To find out how much energy usage level of a room or a building IKE value calculations and compared with the standard IKE value. IKE value will determine the criteria of a room using electricity in this category can be wasteful or not in use electrical energy. When the results were equal to or less than the target IKE, the energy audit activities can be stopped or continued with the hope that IKE values obtained Lower again. The results showed that of the 708 rooms have been evaluated including 136 belonging to wasteful use of electricity, with the savings opportunities that can be done as much as Rp 17.686.222 per month